Defining Suitable Reference Genes for RT-qPCR Analysis on Intestinal Epithelial Cells - Sirakov, Maria; Borra, Marco; Cambuli, Francesca Maria; Plateroti, Michelina (Molecular biotechnology, 2013)
The study of the mammalian intestinal epithelium concerns several aspects of cellular and molecular biology. In fact, most of these studies aim to define molecular components or mechanisms related with the control of stemness and the balance between cell proliferation and differentiation in physiopathological conditions. It is worth mentioning that real-time quantitative reverse transcription-polymerase chain reaction (RT-qPCR) approaches are commonly used, but only a few studies are available regarding suitable reference genes to normalize gene expression data. The present study was designed to validate potential reference genes in freshly isolated proliferating or differentiated epithelial cells from the mouse intestine. We also extended our analysis to the IEC6 intestinal epithelial cells, as a promising model to study intestinal physiopathology in vitro. The stability of six potential reference genes (Hprt1, Ppia, Gapdh, Rplp0, Ppib, and Vil1) has been tested both in epithelial cells isolated from the mouse intestine and in the IEC6 cell line. The software programs—geNorm and Normfinder—were used to obtain an estimation of the expression stability of each gene and, by comparing the results, to identify the most suitable genes for RT-qPCR data normalization. These multiple approaches allowed us to select different suitable reference genes for the correct quantification of mRNAs depending on the differentiated or proliferative nature of the cells.